2011
DOI: 10.1007/s11192-011-0410-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring regional science networks in China: a comparison of international and domestic bibliographic data sources

Abstract: Bibliographic databases are frequently used and analysed for the purpose of assessing the capacity and performance of individual researchers or entire research systems. Many of the advantages and disadvantages are the subject of continued discussion in the relevant literature, although only rarely with respect to the regional dimension of scientific publication activity. The importance of the regional dimension of science is reflected in many theoretical concepts, ranging from innovation system theories to ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The works have also resulted into various scientific papers (Hennemann, Wang, & Liefner, 2011;Hullmann & Meyer, 2003) and patents (Jaffe & Trajtenberg, 2002;Xiang et al, 2013).…”
Section: Knowledge Spillovers and Innovation Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The works have also resulted into various scientific papers (Hennemann, Wang, & Liefner, 2011;Hullmann & Meyer, 2003) and patents (Jaffe & Trajtenberg, 2002;Xiang et al, 2013).…”
Section: Knowledge Spillovers and Innovation Networkmentioning
confidence: 99%
“…With the help of theory and empirical researches conducted abroad, several scholars have begun to examine this issue in China using papers or patents. Taking specific areas, Hennemann et al (2011) have studied biotechnological knowledge networks between international and provinces. The findings of their research stress that Beijing is prominent in both the networks, while Hong Kong and Guangdong are more important in the international networks, and Shaanxi occupies a high position in the provincial networks.…”
Section: Urban Innovation Network In Chinamentioning
confidence: 99%
“…Nevertheless, we acknowledge that the use of the SCI comes with the biases inherent in this type of data. For instance, Hennemann et al (2011) point out that there can be differences when using domestic bibliographic databases as opposed to international ones. However, given that science policy makers attach increasing value to the international visibility o f research, we believe that our focus on the rise of Chinese science as measured by SCI publication counts is justified (Jonkers, 2010, page 13).…”
Section: Why Use Cities As the Unit Of Analysis?mentioning
confidence: 99%
“…Moed () and Liang () have suggested using national Chinese bibliometric databases to assess Chinese research performance. Some researchers have combined WoS with national Chinese bibliometric databases and report many differences between the databases when investigating coauthorship networks (Hennemann et al, ), regional publications (Liang, ), as well as citation analysis (Meho & Yang, ). Taken as a whole, these results suggest that the WoS and national Chinese bibliometric databases tell different stories about Chinese research, although it is not clear how much they differ.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many scholars have concluded that the WoS is not an appropriate tool to measure Chinese research performance (Guan & He, ; Jin & Rousseau, ; Zhou & Leydesdorff, ), as significant differences have been found in the coverage of international and national Chinese bibliometric databases (Hennemann, Wang, & Liefner, ; Meho & Yang, ). Although previous work has attempted to explain differences between WoS and Chinese bibliometric databases by looking at journal hierarchies and citation relations (Zhou & Leydesdorff, ), or regional publications (Liang, ), no research has yet analyzed the discrepancies at the level of authors.…”
Section: Introductionmentioning
confidence: 99%